European Union ERAMUS project - Chan, Margaret Kit Yok (Universiti Teknologi MARA, Sarawak, 2017)
The purpose of Blended Learning for Teacher Educators in Asia and Europe project (BLTeae) consisting of 8 working packages (WP) is to support teacher educators' professional development through blended learning based on innovative constructivist theories identifying the following concrete outputs from its work based on the text of the proposal submission: blended learning courseware with online and face-to-face training offer, a collaborative and reflective learning community, innovative teaching practice scenarios, a curriculum design for teacher training.